ASSESSMENT OF THE COMPANY’S SOLVENCY USING FOREIGN EXPERIENCE - Basshieva Zhangul (Scientific Journal of Pedagogy and Economics, 2021)
In modern conditions, the issue of liquidity and solvency of the enterprise is very relevant. And effective management of liquidity and solvency of the enterprise is the allocation of resources that allow you to convert assets into cash in the short term. In order to increase the efficiency of solvency management, it is necessary to constantly analyze and objectively assess its level. The solvency of the enterprise is determined to be able to repay short-term liabilities in a timely manner and continue to operate through current assets. Therefore, the solvency of an enterprise can be attributed to the fact that the amount of current assets exceeds current liabilities. Identify a system of financial indicators that affect the solvency of the enterprise and conduct a comprehensive scientific analysis on the example of the enterprise. During the analysis period, it is possible to identify the factors that affect the loss of solvency of the enterprise, respectively, to organize countermeasures, as well as to organize an optimal financial model of the company to increase solvency. The stability of the company’s financial indicators also affects the borrowed capital. If an enterprise has more financial attractiveness, its capabilities increase. However, there is an increase in its financial risk. Because the company may threaten the preliminary loss of debts. It is necessary to optimize the inventory of goods intended for the sale of finished products and control the consumption of material resources of the enterprise in the process of providing services, manufacturing products and performing work. In the case of timely payment for services provided by the enterprise (rejection of low-income customers and consumers), it is necessary to develop measures that ensure the possibility of individual impact on the consumer, depending on his ability to pay.